Marine benthic diatoms in the newly discovered coral reefs, off Basra coast, Southern Iraq - Al-Handal, Adil Y.; Thomas, Evan W.; Pennesi, Chiara (Phytotaxa, 2018)
The recent discovery of coral reefs off Basra, Southern Iraq, have prompted the investigation of marine benthic assemblages in this unexplored ecosystem. These corals are thriving in an environment with conditions not usually considered typical for reefs, such as increased turbidity, temperature fluctuation, and currents. This study documents 96 diatom taxa belonging to 33 genera, 18 of which were not previously known from the Arabian (Persian) Gulf including six taxa of Amphora and five of Campylodiscus. The most common genera were Amphora with 17 taxa, Nitzschia with 10 taxa, and Navicula with nine taxa. Most notably is the very rare occurrence of Mastogloia, which has been previously documented as speciose in coral reef habitats. Similarly, araphid and monoraphid species were uncommon in these diatom communities. The large species of the epipelic diatom Trachyneis are well represented and appeared commonly in all samples examined.